2006
DOI: 10.3341/kjo.2006.20.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Visual Improvement in High Myopic Amblyopic Adult Eyes following Phakic Anterior Chamber Intraocular Lens Implantation

Abstract: PurposeTo evaluate the efficacy and safety of angle-supported phakic anterior chamber intraocular lenses in amblyopic adult eyes with very high myopia.MethodsWe evaluated 12 eyes in nine patients with very high myopic amblyopia who received angle-supported phakic intraocular lenses (Phakic 6H®) and followed them for more than six months. Uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), and complications were evaluated. A satisfaction score was rated by patients using a 5-point (1~5) numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…Astle and colleagues found that 30.3 per cent of patients with refractive amblyopia after laser‐assisted subepithelial keratectomy (LASEK) had a five to six line improvement in VA. Similar results were also reported in phakic intraocular lens implantation . Some patients classified as refractive amblyopes may not have been corrected in appropriate ways to induce emmetropia .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Astle and colleagues found that 30.3 per cent of patients with refractive amblyopia after laser‐assisted subepithelial keratectomy (LASEK) had a five to six line improvement in VA. Similar results were also reported in phakic intraocular lens implantation . Some patients classified as refractive amblyopes may not have been corrected in appropriate ways to induce emmetropia .…”
Section: Discussionsupporting
confidence: 83%
“…The Visian implantable collamer lens (ICL) (STAAR Surgical Inc, Nidau, Switzerland), a posterior chamber phakic intraocular lens (PIOL) provides safe, effective, predictable and stable visual and refractive outcomes for high myopia . In addition, this surgical procedure largely improves the visual acuity (VA) of highly myopic eyes . Although many patients with high myopia have poor pre‐operative spectacle visual acuity (SVA), a considerable number of patients unexpectedly achieve a normal or largely improved VA after surgery …”
mentioning
confidence: 99%
“…To date, this has been documented only in children aged 3 to 7 years (in PEDIG studies 27 ). Kwon et al 28 made the assumption that numerous patients classified as amblyopia may not have been treated with the appropriate therapy to induce an appropriate emmetropic condition. Moreover, correction of astigmatism at the corneal plane instead of the spectacle plane may be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…In Stage 2, 310 articles were retrieved, 229 of which satisfied Stage 3 criteria; 123 articles eventually satisfied Stage 4 standards and were included in the study. There were 24 articles on AC pIOLs, 4,11,12,15,23,26,27,53,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] 5 of which described previously published cases. 15,53,62,63,69 There were 50 articles on IF pIOLs, 3,6,[8][9][10]28,30,31,33,[35][36][37][38][39] 14 of which covered formerly published cases.…”
Section: Literature Analysismentioning
confidence: 99%